Practical Apache Struts 2 Web 2.0 Projects - Roughley, Ian (Apress : Imprint: Apress, 2007)
Apache Struts has long provided Java developers with a powerful framework for building extensible, maintainable web applications. Yet the version 2 release takes developers' capabilities to the next level, having integrated Ajax support, the ability to easily integration with the Spring framework, and the ability to take full advantage of POJOs. Practical Apache Struts 2 Web 2.0 Projects shows you how to capitalize upon these features to build next-generation web applications that both enthrall and empower your users. Gain an in-depth understanding of the Struts framework, with special attention paid to key version 2 features Learn how to take advantage of Web 2.0 concepts alongside Struts 2 to build next-generation web sites Follow along with the introduction of important concepts and development techniques by way of a web site project closely resembling what you might encounter in any enterprise environment.